3D-architectured Pt-carbon electrodes for PEM fuel cells with tuned porosity and ionomer distribution-a micromanaged approach for improving activation, ohmic, and mass transport characteristics - Singh, Mayank U.; Mathew, Grigory; Kurungot, Sreekumar (ACS Applied Energy Materials, 2025)
The conventional catalyst layer in Proton Exchange Membrane Fuel Cells (PEMFCs) suffers the limitation of masked active sites, hindered proton transportation, excessive water clogging, and irregular ionomer distribution, resulting in an underutilized catalyst. To overcome these challenges, an innovative catalyst layer (CL) is constructed by aligning Vulcan carbon (VC) particles along a 3D carbon nitride interconnected network originating from a melamine sponge. This forms a robust scaffold rich in anchoring sites like sulfur and nitrogen for the Pt nanoparticle. The resultant 3D CL exhibits a doubled through-plane proton transport conductivity from 23 to 41 mS cm-1, delivering a 17.3% increase in the current density at 0.60 V compared to a conventional VC CL. This strategy enables enhanced ionomer incorporation, yielding a 19.60% enhancement in the ionomer coverage over the Pt without sacrificing the porosity, as verified by a mercury porosimeter. Kelvin probe force microscopy confirms a more uniform electron density across the 3D CL, in contrast to the traditional CL, suggesting uniform coverage. The advanced porosity and structure of the 3D CL allow the mass transport regions to shift to higher current densities, with an increase of 0.30 A cm-2 at 0.50 V compared to the VC CL. The improved ionomer coverage also demonstrates 19% lower voltage degradation at 0.80 A cm-2. Further, the impedance mapping across the entire current range graphically illustrates the 3D CL's advantage in the activation, Ohmic, and mass transport regions, showing a parabolic profile with a flattened bottom attributed to the reduced Ohmic resistance and its extension to delay the mass transport losses.
Keywords: 3D-structured catalyst layer; impedancemapping; ionomer coverage; low-temperature proton exchange membranefuel cell (LT-PEMFC); mercury porosimeter; proton resistance; triplephase boundary (TPB)

Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater

Hot injection assisted electronically modulated twin and grain boundary rich sub-2 nm pt3co alloy resistant to phosphate ion for PEMFCs - Singh, Mayank U.; Jadhav, Swapnil D.; Shivankar, Bhavana R.; Pandikassala, Ajmal; Kumar, Yogesh; Krishnamurty, Sailaja; Vinod, C. P.; Kurungot, Sreekumar (Small, 2025)
Modulation of the electronic d-band center, structural defects (line defects), and particle size of Pt3Co alloy electrocatalyst have huge significance in elevating its electrochemical oxygen reduction reaction activity. Deviating from traditional high-temperature strategies, the current work focuses on ripening these benefits by implying a simple economically viable hot-injection-assisted modified polyol process. A conclusive control over decrementing particle size starting from 2.7 to 1.3 nm, an increasing degree of strain (twin boundary), and shifting of the d-band center away from the Fermi level are obtained via varying the temperature to which the solution is injected. The catalyst prepared via the injection at 200 degrees C (Pt3Co(1.3 t,g-b)/fVC-200) has delivered an electrochemical surface area of 84 m(2) g(Pt)(-1) with the onset and half-wave potentials of 0.980 and 0.858 V, respectively, versus RHE and a limiting current of -6.0 mA cm(-2) with stability till 20k cycles. In the high-temperature proton exchange membrane fuel cell Pt3Co(1.3 t,g-b)/fVC-200-based cell has outperformed Pt/C rendering 600 mWcm(-2) under H-2-Air compared to 529 mWcm(-2) of Pt/C with 20% lower Pt loading and double the stability due to enhanced resistance toward phosphoric acid for accelerated voltage cycling. A similar enhancement is seen while employing the catalyst for low-temperature fuel cells.
Keywords: electrocatalyst; grain boundary; hot injection synthesis; modified polyol process; oxygen reduction reaction; proton exchange membrane fuel cell; Pt3Co alloy; twin boundary; valance band X-ray photoelectron spectroscopy

Pt-based 3D electrocatalyst with process-friendly features for PEMFCs possessing fast activation and improved mass-transfer properties - Pandikassala, Ajmal; Nadumattuvayil, Varsha; Singh, Mayank U.; Jadhav, Swapnil D.; Yoyakki, Athira; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Polymer-electrolyte-membrane fuel cells (PEMFCs) face the challenges like slow oxygen reduction reaction (ORR) kinetics and limited mass transport at high current densities, which affects their performance. The efficient water removal from the cathode is essential to improve oxygen diffusion. Addressing this, a catalyst is presented with platinum (Pt) nanoparticles distributed within a 3D carbon network (Pt/3DPDC) derived from the polydopamine-coated melamine foam. This unique architecture enhances Pt utilization and water management due to its high porosity and ample free spaces, providing a process-friendly feature for the electrode under PEMFC conditions. The pores and accessible texture of the 3D polydopamine derived carbon (3DPDC) framework facilitate ionomer uptake during the electrode fabrication, extending the active triple-phase boundary and improving the membrane electrode assembly (MEA) performance. The high porosity of Pt/3DPDC is mitigated by adding a small amount of commercial fuel cell catalayst (Pt/C), which maintains the effective catalyst number density per unit area by utilizing the excess porosity of the 3DPDC framework. This controlled interplay of the unique catalyst structure and spatially confined distribution of Pt/C within the Pt/3DPDC framework offers fast activation, reduced electrode flooding, and improved current densities across the operating potential window. This carefully engineered catalyst, designed through bottom-up strategies, is a promising electrocatalyst for practical PEMFC applications.
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

Proton conductivity in a copper(II) bipyridine glycoluril complex: the synergistic role of coordinated water and hydrogen-bonded networks - Khatavkar, Medhavi D.; Panday, Rishukumar; Singh, Mayank U.; Kurungot, Sreekumar; Kumbhar, Avinash S. (Inorganica Chimica Acta, 2026)
A dinuclear complex of copper(II) and bipyridine glycoluril (BPG) ligand is synthesized, characterized, and structurally examined by single-crystal X-ray diffraction. The complex [Cu2(BPG)2(NO3)2(H2O)4](NO3)2 center dot 5H2O (complex (1)) further forms a supramolecular network sustained by H-bonds between NH/C=O of BPG, coordinated/free water molecules, and nitrate anions. The complex exhibits a proton conductivity of 5.99 x 10_ 3 S center dot cm_ 1 at 90 degrees C and 95 % relative humidity (RH) with activation energy value Ea 0.35 eV, suggesting the Grotthuss proton transport mechanism. This value is consistent with those reported for proton-conducting systems in which coordinated water molecules play a critical role in facilitating efficient proton hopping across hydrogen-bonded networks.
Keywords: Coordinated water; Copper(II) complex; H -bonding; proton conduction; Supramolecular networks